Juvenile Justice and Punishment of Girls in Brazil - Jalusa Silva de Arruda; Natasha Maria Wangen Krahn (Oñati Socio-Legal Series)
This article presents a bibliographical review of research carried out within the scope of the Brazilian postgraduate programs that studied the execution of socio-educational measures on girls in the juvenile justice system and that adopted gender studies or feminist approaches as their theoretical perspective. Theses and dissertations that have been produced on the theme were identified and eventual gaps in these works were indicated, thus contributing to new possibilities of research on the subject in the country. We concluded that the studies developed in the scope of the postgraduate programs in addition to other studies on the subject give an overview of the situation of girls in the Brazilian socio-educational system, but that it is still necessary to further analyze modes of punishment that are especially applied to girls and interpret them considering the specificities of the Brazilian social reality, especially regarding the intersection between the social categories gender, race, class and generation.